2020
DOI: 10.1111/1750-3841.14989
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the antimicrobial and antibiofilm effects of cinnamaldehyde against Campylobacter spp. using cell surface characteristics

Abstract: Campylobacter species are known as biofilm‐forming bacteria in food systems. The aim of this study was to evaluate the antimicrobial and antibiofilm effects of cinnamaldehyde against Campylobacter jejuni and Campylobacter coli isolated from chicken meat. The biofilm‐forming C. jejuni and C. coli strains from chicken meat were investigated using minimum inhibitory concentration (MIC) and Campylobacter spp. characteristics. The MIC value was 31.25 µg/mL for the Campylobacter strains tested. Cinnamaldehyde had an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Albano et al confirmed that CA had the ability to reduce the growth of Staphylococcus epidermidis in planktonic state, inhibit biofilm formation and eradicate formed biofilm [ 12 ]. Yu et al found that Campylobacter strains treated with 15.63 µg/mL CA exhibited significantly decreased bacterial auto-aggregation, motility, exopolysaccharide production and soluble protein levels, which proved that it had the ability to remove biofilm [ 13 ]. CA also had an inhibitory effect on Candida albicans by inhibiting the release of its virulence factors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Albano et al confirmed that CA had the ability to reduce the growth of Staphylococcus epidermidis in planktonic state, inhibit biofilm formation and eradicate formed biofilm [ 12 ]. Yu et al found that Campylobacter strains treated with 15.63 µg/mL CA exhibited significantly decreased bacterial auto-aggregation, motility, exopolysaccharide production and soluble protein levels, which proved that it had the ability to remove biofilm [ 13 ]. CA also had an inhibitory effect on Candida albicans by inhibiting the release of its virulence factors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different classes of molecules, such as: triglycerides, fatty acids, and small fractions of natural antioxidants (Attama et al, 2006), exert several therapeutic effects, as analgesic, antimicrobial, anti-inflammatory, antifungal, and antineoplastic (Orhan et al, 2010). The antimicrobial and antibiofilm activities of different natural lipids against CJ have been reported, as observed for oregano and cinnamon essential oils (Clemente et al, 2020;Yu et al, 2020). However, despite these combined therapeutic properties, the clinical use of vegetable lipids-mainly the essential oils-are prevented, due to its physicochemical instability, insolubility, high toxicity, volatility, and photosensitivity (Odeh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The biofilm assay was conducted using the method described by Yu et al [ 22 ], with some modifications. To investigate the inhibition effect on the formation of biofilms, bacterial cultures were diluted to a final concentration of 1.0 × 10 5 CFU/mL, and 50 μL of each was mixed in a 96-well plate with volume equivalent to that of ε-PL, with concentrations ranging from 1/2 × MIC to 2 × MIC, using a non-treated TSB as a control.…”
Section: Methodsmentioning
confidence: 99%